Assessment of innovative PLA biopolymer compositions with plant waste fillers. (September 2022) - Jałbrzykowski, Marek; Oksiuta, Zbigniew; Obidziński, Sławomir; Czyżewska, Urszula; Osiecki, Tomasz; Kroll, Lothar; Joka Yildiz, Magdalena
Highlights: Innovative thermoplastics bio-resorbable composite materials based on polylactic acid (PLA) with onion and buckwheat husks were proposed. Composite materials with addition of 10, 20, 30 wt% of onion or buckwheat husks were prepared by extruding PLA with the filler following by pressing using a hydraulic press with a pressure of 10 kN. Mechanical and thermo-physical properties of the composite materials were tested, with a particular attention to their degree of crystallinity. 10% of filler addition has a beneficial effect on an increase in elongation and degree of crystallinity of composite material. Abstract: This paper presents a proposition of innovative thermoplastics bio-resorbable composite materials based on polylactic acid. The compositions were prepared as an alternative to traditional biodegradable polymers, using grounded and dried plant waste in the form of buckwheat husks and dried onion husks. The main goal of the research was to develop new biopolymers prepared by extrusion for a wide range of industrial applications. Composite samples were made with the addition of 10, 20 and 30 wt% of onion or buckwheat husks and their mechanical and thermo-physical properties were examined, with particular emphasis on the degree of crystallinity. The conducted tests showed that increasing the amount of filler decreases the mechanical properties of the composite, with the exception of the elongation at break, which slightly increased. Moreover, the 10% addition of waste positively influences the increase in the degree of crystallinity of the samples.